PENGARUH PEMBELAJARAN MEDIA INTERAKTIF TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Nabillah Putri Handayani; Fidrayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning outcomes are the results achieved by students after they have participated in learning activities. The aim of this research is to determine the effect of interactive learning media on student learning outcomes in elementary schools. By implementing models, models and the influence of learning media that suit students, learning outcomes will be maximized. The method used in this research is the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) method. The prism method was used to compare research results from several sources for the 2015-2024 period, only covering topics related to learning outcomes and interactive learning media. Therefore, many students are not able to get optimal learning results, this is because there are many influencing factors, one of which is the learning methods and media used by teachers who are not able to provide interest and help students achieve good understanding.   Keywords: interactive learning media, learning outcomes, elementary school